Anthropologists and their traditions across national borders. - Darnell, Regna; Gleach, Frederic W. (Histories of anthropology annual., 2014)
Volume 8 of the Histories of Anthropology Annual series, the premier series published in the history of the discipline, explores national anthropological traditions in Britain, the United States, and Europe and follows them into postnational contexts. Contributors reassess the major theorists in twentieth-century anthropology, including the work of luminaries such as Franz Boas, Claude Lévi-Strauss, Bronisław Malinowski, A. R. Radcliffe-Brown, and Marshall Sahlins, as well as lesser-known but important anthropological work by Berthold Laufer, A. M. Hocart, Kenelm O. L. Burridge, and Robin Ridington, among others. These essays examine myriad themes such as the pedagogical context of the anthropologist as a teller of stories about indigenous storytellers; the colonial context of British anthropological theory and its projects outside the nation-state; the legacies of Claude Lévi-Strauss’s structuralism regarding culture- specific patterns; cognitive universals reflected in empirical examples of kinship, myth, language, classificatory systems, and supposed universal mental structures; and the career of Marshall Sahlins and his trajectory from neo-evolutionism and structuralism toward an epistemological skepticism of cross- cultural miscommunication -- Présentation de l'éditeur.